Development of Flexible Semiconductors Based on g-C 3 N 4 /Cu 2 O P–N Heterojunction for Triboelectric Nanogenerator Application - Supakarn Worathat; Utchawadee Pharino; Saichon Sriphan; Surasak Niemcharoen; Wisut Thitirungraung; Rangson Muanghlua; Te‐Wei Chiu; Naratip Vittayakorn (Integrated ferroelectrics, 2023)
AbstractThis research aims to develop flexible semiconductors for triboelectric nanogenerator (TENG) applications. The sample powders of graphitic carbon nitride (g-C3N4) and copper (I) oxide (Cu2O) as N-type and P-type semiconductors, respectively, were synthesized. The semiconductors were prepared to be a composite film with alginate. The structure, morphology, and purity of the N- and P-type semiconductors were characterized using X-Ray diffraction and scanning electron microscopy techniques. Through the optical characterization, the N-type semiconductor showed the calculated energy band gap of 2.80 eV, while the P-type semiconductor was 1.90 eV. The P–N junction property of prepared samples was confirmed using a nonlinear current–voltage characteristic. After that, two flexible semiconductors were frictional paired for TENG. Through a vertical contact-separation mode, the P–N junction-based TENG produced a maximum output voltage and current of 3.90 V and 0.44 µA, respectively, with a maximum output power of 0.35 µW at 10 MΩ. In summary, the present work achieved the preparation of flexible P- and N-type semiconductors. The feasibility to harvest the mechanical energy was demonstrated in the TENG configuration. This idea is crucial for the future development of flexible harvesting/sensing devices using a novel concept.Keywords: P-type semiconductorN-type semiconductorP–N Junctiontriboelectric nanogenerator Disclosure StatementNo potential conflict of interest was reported by the author(s).Additional informationFundingThis work was supported by KMITL under the Grant number KREF156601.The work of Supakarn Worathat thanks to funding support from the Faculty of Science, King Mongkut's Institute of Technology Ladkrabang (KMITL) under Grant no. RA/TA 2565-M-001. The work of S. Sriphan was funded by King Mongkut's University of Technology North Bangkok, Contract no. KMUTNB-65-KNOW-05.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; ZnO doping and properties